STEM Integration in Karate Sport as Physics Learning Media: Development, Validation, and Analysis of Student Learning Outcomes on Impulse and Momentum Materials - RA Sania Noviana; Ida Sriyanti; Wahyu Indra Bayu; Nor Farahwahidah binti Abdul Rahman (Postgraduate, University of Mataram, 2025)
Creative thinking skills are essential competencies in the 21st century, involving cognitive processes and divergent thinking to generate innovative solutions from various perspectives. This study aims to develop and implement a STEM-based learning approach integrated with physics, focusing on impulse and momentum, to improve students' creative thinking skills. Karate is utilized as a contextual medium to facilitate real-life application of physics concepts. The research applies the Research and Development (R&D) method using the 4D model: Define, Design, Develop, and Disseminate. Validation involved nine experts, consisting of lecturers and teachers, who provided feedback to refine the developed e-module. Content validity was assessed using the Content Validity Ratio (CVR) and Content Validity Index (CVI), both reaching 1.00 (100%) across all aspects such as content relevance, Problem-Based Learning (PBL) suitability, ability to assess creative thinking, and design feasibility. Product trials with 101 senior high school students demonstrated significant improvement in creative thinking skills, as shown by an N-Gain score of 0.72. These findings indicate that the developed STEM-based e-module is effective in enhancing students' understanding of physics through contextual and engaging learning.